Labor Market Discrimination and Racial Differences in Premarket Factors - Pedro Carneiro; James Joseph Heckman; Dimitriy V. Masterov (Institute for the Study of Labor (IZA), 2005)
We investigate the relative significance of differences in cognitive skills and discrimination in explaining racial/ethnic wage gaps. We show that cognitive test scores taken prior to entering the labor market are influenced by schooling. Adjusting the scores for racial/ethnic differences in education at the time the test is taken reduces their role in accounting for the wage gaps. We also consider evidence on parental and child expectations about education and on stereotype-threat effects. We find both factors to be implausible alternative explanations for the gaps we observe. We argue that policies need to address the sources of early skill gaps and to seek to influence the more malleable behavioral abilities in addition to their cognitive counterparts. Such policies are far more likely to be effective in promoting racial and ethnic equality for most groups than are additional civil rights and affirmative action policies targeted at the workplace.
Keywords: J31; 330; ability; test scores; gaps; education; Arbeitsmarktdiskriminierung; Lohndifferenzierung; Rasse; Ethnische Gruppe; Bildungsertrag; Bildungsverhalten; Qualifikation; Vereinigte Staaten